Getting it right: Canadian intelligence assessments on Iraq, 2002-2003. Issue 7 (9th November 2020) - Barnes, Alan
ABSTRACT: The partial release of Canadian intelligence assessments on Iraq during 2002 and 2003 has made it possible for the first time to examine the role that intelligence played in informing the Chrétien government's decisions in the lead-up to the war in Iraq. Canadian assessments of US policy on Iraq, Baghdad's weapons of mass destruction capabilities, the regional implications of an invasion, and the subsequent internal instability of Iraq proved to be largely accurate, in contrast to much of the analysis on Iraq by other members of the Five Eyes intelligence partnership.